PENGARUH BAURAN PEMASARAN 7P (PRODUCT, PRICE, PLACE, PROMOTION, PEOPLE, PROCESS, PHYSICAL EVIDENCE) TERHADAP KEPUTUSAN BERKUNJUNG KE AGROWISATA TAMAN BUNGA NUSANTARA - Malia, Rosda (JURNAL AGRITA, 2025)
Taman Bunga Nusantara is one of the agritourisms located in Cianjur Regency, West Java. Attractions in West Java, especially Cianjur Regency, continue to emerge and have the potential to become new competitors for Taman Bunga Nusantara. Taman Bunga Nusantara needs to pay attention to the marketing mix so that these tourist destinations can still be attracted by tourists. This study aims to analyze the effect of Product, Price, Place, Promotion, People, Process, Physical Evidence partially and simultaneously on the decision to visit Taman Bunga Nusantara agrotourism. The data analysis methods used in this study include: descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, correlation analysis, simple linear regression analysis, t test, F test, multiple linear regression analysis and multiple determination coefficient (R²). The sampling technique used purposive sampling with a total of 100 respondents. Based on the results of the t test, it is known that partially the variables Product (X1), Price (X2), Place (X3), Promotion (X4), People (X5), Process (X6) and Physical Evidence (X7) have a positive and significant effect on visiting decisions. While the F test results show that simultaneously, the 7P marketing mix variables have a significant effect on visiting decisions.